Proposal of a new category of lunar regolith simulants: reduced particle-density simulants that exhibit equivalent self-weight in Earth gravity to native regolith in lunar gravity - Pratnekar, Marko; Garg, Vivek; Kaur, Baldeep; Bradley, Michael S. A.; Cullen, David C. (Elsevier, 2025)
Current “normal density” lunar regolith simulants used in Earth gravity can be viewed as a poor replication of bulk material handling behaviour of lunar regolith in lunar gravity. The six-times greater self-weight of such normal simulants on Earth compared to the Moon can be the viewed as the underlying cause. The use of such normal simulants in Earth gravity as part of technology development for lunar use may fail to adequately predict lunar behaviour and result in sub-optimal outcomes. This paper proposes a new class of reduced self-weight lunar regolith simulants to minimise this issue. The current work elaborates the case for this new class of lunar regolith simulants with reduced particle density of one-sixth native lunar regolith resulting in reduced self-weight. To justify further this approach a series of studies are reported to highlight the expected differences between the current and proposed simulant uses. First, analytical arguments are used based around Jenike theory and the concept of Bond Number to highlight expected differences. Second, Discrete Element Method simulation is used show the expected difference in behaviour between the two simulants classes. Third, a laboratory breadboarded discharge hopper is used to demonstrate behaviour differences between normal and reduced self-weight stimulants. Additionally, a list of requirements for such reduced self-weight simulants is proposed. The work concludes that the proposed new class of reduced particle density lunar simulants appears to have value and should be further pursued by the relevant communities.
Keywords: Aerospace & Aeronautics; 4001 Aerospace engineering; Materials handling; Lunar; Bulk materials; Reduced gravity; Regolith simulants; Reduced-density simulants; Discrete element method; Discharge hopper